STRATEGI PENGELOLAAN ZAKAT PRODUKTIF DALAM PENGENTASAN KEMISKINAN: STUDI KASUS BAZNAS KOTA BANDAR LAMPUNG - Alfin Aziz; Muhammad Iqbal Fasa; Suharto Suharto (LP2M Universitas Bina Bangsa, 2022)
Discusses the management of productive zakat and its impact in poverty alleviation efforts carried out by various zakat management organizations in Indonesia. The urgency of productive zakat management has been regulated in Law Number 23 of 2011 concerning zakat management. In addition, optimal and professional management of productive zakat will always provide solutions to the main problem in the structure of zakat recipients (front of ashnaf), namely the poor. Paradigmatically, zakat as an instrument of the pillars of Islam has a significant economic and social impact in alleviating poverty, so that zakat recipients, especially the poor, are slowly empowered into various strategic sectors which can eventually become donors or new muzakki. The zakat management organization described in this article programmatically explores the main problems of the poor by making various community empowerment programs into the main sectors, namely education, social, health, and disaster. While the evaluation is to measure the development of national zakat which can be an indicator of the impact of zakat on the lives of mustahik, zakat organization institutions, and the role of the government, in Indonesia the National Zakat Index has been compiled